DIGITAL MINDSET IN PROMOTING REGIONAL TRADITION AND BASIS OF COMMUNICATION WITH PRIVACY IN SOCIAL MEDIA - Fina Carla Rettobjaan, Vitalia; Bagus Aristayudha, AA Ngurah; Aryanata, Nyoman Trisna; Jaya, Putu Prisa; Widnyani, Ni Made (LPPM Univ. Ibn Khaldun Bogor, 2023)
Digital Mindset is a mindset formed by the development of digital technology. Communities are required to be able to use technology in the midst of changes that occur. This change has an impact on the way people open up opportunities to market the area with social media. This convenience provides answers to existing problems regarding the slow introduction of uniqueness in traditional villages which can actually become tourist areas. The purpose of this activity is to provide basic education and training on the use of social media for promotion with Instagram media, and to limit oneself to privacy, steps and making privacy to stay safe in using social media. This activity was carried out in the Bukian Traditional Village, Gianyar. From the results of the descriptive analysis, data was obtained that out of 183 people who had been given information, 123 (67.21%) had a good understanding of building a digital mindset and communicating privacy on social media accounts. As many as 60 people (32.79%) quite well understand this understanding of digitalization. The general public already has a good understanding of building a digital mindset and good communication on social media.